Recurrence and survival after surgery for pancreatic cancer with or without acute pancreatitis - Feng, Qian (World J Gastroenterol, 2019)
BACKGROUND: In pancreatic cancer, acute pancreatitis (AP) is a serious morbidity, but its negative effect on long-term outcomes remains to be elucidated. AIM: To investigate the effects of AP on the tumor recurrence pattern of pancreatic ductal adenocarcinoma (PDAC) and tumor-specific survival. METHODS: The medical records of 219 patients with curative pancreatectomy for pancreatic cancer at the Pancreatic Surgery Center of West China Hospital from July 2012 to December 2016 were analyzed retrospectively. The severity of acute pancreatitis was classified according to the Atlanta classification of AP. The patient demographics and tumor characteristics were assessed. Early recurrence was defined as a relapse within 12 mo after surgery. Overall and disease-free survival and recurrence patterns were analyzed. Mild acute pancreatitis was excluded because its negative effects can be negligible. RESULTS: Early recurrence in AP group was significantly higher than in non-AP group (71.4% vs 41.2%; P = 0.009). Multivariate analysis of postoperative early recurrence showed that moderate or severe AP was an independent risk factor for an early recurrence [odds ratio (OR): 4.13; 95% confidence interval (CI): 1.41-12.10; P = 0.01]. The median time to recurrence was shorter in patients with AP than in those without (8.4 vs 12.8 mo; P = 0.003). Multivariate analysis identified AP as an independent prognostic factor for overall survival [relative risk (RR): 2.35; 95%CI: 1.45-3.83] and disease-free survival (RR: 2.24; 95%CI: 1.31-3.85) in patients with PDAC. CONCLUSION: Patients with moderate or severe acute pancreatitis developed recurrences earlier than those without. Moderate or severe AP is associated with shorter overall and disease-free survival of patients with PDAC.